A floating pulsatile drug delivery system based on hollow calcium pectinate beads - Somani, V G; Shahi, S R; Udavant, Y K; Atram, S C; Satpute, R; Shinde, N M (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present work is to envisage and develop hollow calcium pectinate beads for floating pulsatile release of aceclofenac intended for chronopharmacotherapy. Floating pulsatile concept was applied to increase the gastric residence of the dosage form having lag phase followed by a burst release. The method used for the development of the beads was a simple process of acid-base reaction during ionotropic cross linking. The floating beads obtained were porous, hollow with a bulk density <1 and had an Ft50 of 14-24 h. The floating beads showed a two-phase release pattern with initial lag phase during floating in an acidic medium followed by rapid pulse in phosphate buffer. The approach indicates the use of hollow calcium pectinate microparticles as a promising floating pulsatile drug delivery system for site- and time-specific release of drug acting as per chronotherapy of disease.